Odpowiedzi

2009-05-19T15:17:04+02:00
1. 2(x-3)-(3x-1)=5
2. -(x+1)-2(-1-x)=-4
3. 3(x-2)+2(4-x)=6
4. -2(4-x)+3(2x+1)=-7
5. (x+3)-(2x-1)=1
6. -3(2-x)-2(1-3x)=10

1. 2x-6-3x+1=5
-x=5-1+6
-x=2
x=-2

2. -x-1+2+2x=-4
x=-4+1-2
x=-5

3.3x-6+8-2x=6
x=6+6-8
x=4

4. -2(4-x)+3(2x+1)=-7
5. (x+3)-(2x-1)=1
6. -3(2-x)-2(1-3x)=10

4.-8+2x+6x+3=-7
8x=-7+8
8x=1
x=1/8 (ale chyba to jest źle)

5. x+3-2x+1=1
-x=1-3
-x=-2
x=2

6. -6+3x-2+3x=10
-8+6x=10
6x=10+8
6x=18 \:6
x=3



raczej to jest dobrze ;]
2009-05-19T15:22:23+02:00
1. 2x-6-3x+1=5
-x=5+5
-x=10/(-1)
x=-10

2.-x-1+2+2x=-4
x+1=-4
x=-5

3.3x-6+8-2x=6
x+2=6
x=4

4.-8+2x+6x+3=-7
8x-5=-7
8x=-2/8
x=-1/4

5.x+3-2x+1=1
-x+4=1
-x=-3/(-1)
x=3

6.-6+3x-2+6x=10
9x-8=10
9x=18/9
x=2
raczej TO jest dobrze